Combination of thrombolytic and immunosuppressive therapy for coronavirus disease 2019: A case report. (August 2020) - Papamichalis, Panagiotis; Papadogoulas, Antonios; Katsiafylloudis, Periklis; Skoura, Apostolia-Lemonia; Papamichalis, Michail; Neou, Evangelia; Papadopoulos, Dimitrios; Karagiannis, Spyridon; Zafeiridis, Tilemachos; Babalis, Dimitris; Komnos, Apostolos
Highlights: Immunothrombosis is the basis of many syndromes in patients with COVID-19. The administration of thrombolysis and immunosuppression treatments could be a therapeutic option. Concurrent recombinant tissue plasminogen activator (rt-PA) and tocilizumab infusion led to a significant improvement in the patient presented here. The patient's skin ischemia, cytokine release syndrome (CRS), and acute respiratory distress syndrome (ARDS) resolved. Such therapeutic combinations could prove beneficial for patients with COVID-19. Abstract: In a proportion of patients, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a multisystem syndrome characterized by hyperinflammation, acute respiratory distress syndrome (ARDS), and hypercoagulability. A 68-year-old man with coronavirus disease 2019 (COVID-19) was admitted to the intensive care unit with respiratory failure, cytokine release syndrome (CRS), and skin ischemia – microthrombosis. Specific coagulation and inflammatory markers (D-dimer, ferritin, and C-reactive protein), along with the clinical picture, triggered the trial of recombinant tissue plasminogen activator (rt-PA) and tocilizumab. This was followed by resolution of the skin ischemia and CRS, while respiratory parameters improved. No major complications associated with rt-PA or tocilizumab occurred. The combination of rt-PA with targeted anti-inflammatory treatment could be a new therapeutic option for patients with COVID-19, ARDS, hyperinflammation, and increased blood viscosity.